Analysis of Rhodamine B Content in Eyeshadow Cosmetic Preparations with UV-Vis Spectrophotometer and Butterfly Pea Flower (Clitoria ternatea L.) Extract - Berliyanti, Adella Eka (Universitas Muhammadiyah Gresik, 2024)
In the modern era, maintaining a good appearance is crucial. Many people are out there vying for the most outstanding looks. Many are also eager to spend money to improve their appearance, such as by undergoing various treatments and purchasing numerous cosmetic preparations. One type of cosmetics most often used by people is eyeshadow. As a decorative cosmetic, of course, eyeshadow has colouring content. However, Rhodamine B is still misused, a dangerous dye in eye shadow preparations, because most eye shadow palettes have a red base colour. As a result, the author recognizes the importance of researching to differentiate eyeshadow cosmetics containing Rhodamine B from those that do not, using natural ingredient indicators, given Indonesia's abundance of biodiversity. Rhodamine B may be detected using anthocyanins, natural pigments in various plants; one is butterfly pea flowers. The results of visual observations of the reaction of butterfly pea flower extract and cosmetic samples will then be confirmed using a UV-Vis Spectrophotometer. The qualitative analysis revealed that all eyeshadow samples tested positive for Rhodamine B, as shown by the colour change in the butterfly pea flower extract from blue to purple to pink. The quantitative examination revealed that Rhodamine B concentrations in five samples ranged from 0.419 mg/L to 15.891 mg/L. According to BPOM, cosmetic products should not include Rhodamine B (≤ 0 mg/L).